IT PROJECT RISK MANAGEMENT FOR CLOUD ENVIRONMENT LEVERAGING ARTIFICIAL INTELLIGENCE - Nair, Remya; Meenakumari, J. (International Journal of Research -GRANTHAALAYAH, 2022)
Cloud security contributes to multiple risk parameters like multitenancy, Insecure interfaces/APIs, Malicious Insiders, Malware injections, the lack of information on location of storage of data, the unavailability of details on type of data saved in the same server, hacking. AI or Artificial Intelligence works on pre-collected data and scenarios fed into the computers thereby predicting in advance the possibilities of risk, warning if there is any unusual occurrence in the cloud and proposing the Risk Mitigation plans based on various scenarios. Proactive risk prediction will have a huge impact on risk mitigation, cost saving as well as customer satisfaction. A pilot study has been conducted to ascertain the impact of various risk factors identified by circulating the questionnaire among practitioners from the relevant domains. The questionnaire is circulated among the current industry practitioners and experts in this area and facilitates to conduct the pilot survey on the significance of various risk parameter. The impact of each risk factor is identified and is subjected to analysis. With the help of prediction algorithms, the possibility of occurrence of risk, the impact, and consequences of that particular event, as well as the mitigation strategies could be foretold. This objective of this paper is to propose management perspective of a framework of AI, that can contribute to proactive risk management in cloud. This paper deals only with the management overview of implementation of AI in risk mitigation strategies and not the technical aspects of AI. The futuristic scope of this paper would be a management overview on automation of risk mitigation strategies in cloud platform using AI.